1688 and all that: property rights, the Glorious Revolution and the rise of British capitalism. Issue 1 (10th October 2016) - HODGSON, GEOFFREY M.
Abstract: In a seminal 1989 article, Douglass North and Barry Weingast argued that by making the monarch more answerable to Parliament, the Glorious Revolution of 1688 helped to secure property rights in England and stimulate the rise of capitalism. Similarly, Daron Acemoglu, Simon Johnson, and James Robinson later wrote that in the English Middle Ages there was a 'lack of property rights for landowners, merchants and proto-industrialists' and the 'strengthening' of property rights in the late 17th century 'spurred a process of financial and commercial expansion'. There are several problems with these arguments. Property rights in England were relatively secure from the 13th century. A major developmental problem was not the security of rights but their feudal nature, including widespread 'entails' and 'strict settlements'. 1688 had no obvious direct effect on property rights. Given these criticisms, what changes promoted the rise of capitalism? A more plausible answer is found by addressing the post-1688 Financial and Administrative Revolutions, which were pressured by the enhanced needs of war and Britain's expanding global role. Guided by a more powerful Parliament, this new financial system stimulated reforms to landed property rights, the growth of collateralizable property and saleable debt, and thus enabled the Industrial Revolution.